El Conspirador y Blanca sol, el ideal de hombre/mujer en la novelística de Mercedes Cabello de Carbonera - Barúa Lanchippa, Norma Isabel (2019)
The present article proposes an epistemological analysis of the ideological position Mercedes Cabello de Carbonera offers about the social binomial man/woman developed in her academic articles and in her narrative production. We postulate that the Peruvian writer supports her liberal society agenda based on the roles men and women must play to become the answer to the problems Peru confronted at the end of the XIX century. To do so, we have applied the Theory of Complementarity of Sexes, taking into account Cabello´s ideological thinking and her naturalistic approach, to the protagonists of Cabello’s two last novels, El Conspirador and Blanca Sol; both figures represent the ideal couple towards Peru in the XX century.